1994
DOI: 10.1111/j.1365-2362.1994.tb01082.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus is associated with increased auto‐antibody titers against calreticulin and Grp94, but calreticulin is not the Ro/SS‐A antigen

Abstract: Auto-antibodies against purified human calreticulin were determined by an ELISA in sera from patients with systemic lupus erythematosus (SLE) and from healthy persons or patients without an autoimmune disease. More than 80% of patients with SLE had titers exceeding the highest value obtained in the group without SLE. Almost 30% of the patients had also elevated auto-antibody titers against purified rat grp94, another resident ER-protein of the KDEL-protein family, but not against rat ERp72 (CaBP2), an ER-resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
2
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 35 publications
3
42
2
2
Order By: Relevance
“…Recently, Rokeach et al [18] and Boehm et al [19] were able to demonstrate that calreticulin is not a Ro/SS-A antigen, but we have shown, on the other hand, that human calreticulin is an autoantigen in patients with systemic lupus erythematosus.…”
Section: Introductioncontrasting
confidence: 63%
“…Recently, Rokeach et al [18] and Boehm et al [19] were able to demonstrate that calreticulin is not a Ro/SS-A antigen, but we have shown, on the other hand, that human calreticulin is an autoantigen in patients with systemic lupus erythematosus.…”
Section: Introductioncontrasting
confidence: 63%
“…Interestingly, the average level of serum CRT in RA patients was ∼5-fold higher than that of SLE patients (24.31 6 8.97 versus 4.70 6 1.89 ng/ml; p , 0.05). It has previously been reported that SLE is associated with increased anti-CRT Ab titers (28,29). However, by using the rCRT/392-272-based ELISA, we detected CRT-specific IgG Abs in sera from not only the patient groups but also from control subjects, and average levels of such Abs in the three groups were not significantly different (Fig.…”
Section: Detection Of Soluble Crt In Patient Seramentioning
confidence: 77%
“…[47][48][49][50] Interestingly, anti-CRT IgA titers are more useful than anti-CRT IgG levels for detecting mammary, colorectal, hepatocellular and pancreatic carcinomas, alcoholic hepatitis, refractory celiac disease or primary biliary cirrhosis. 30,[51][52][53] High concentrations of anti-CRT IgA antibodies were more frequently detected in lymph node-positive breast cancers than IgG antibodies, but failed to correlate with CRT membrane expression.…”
Section: Discussionmentioning
confidence: 99%